CREATING A SENSE OF BELONGING: A LITERATURE REVIEW OF THE ROLE OF INCLUSIVE LEADERSHIP IN ENHANCING EMPLOYEE RETENTION IN GLOBAL ORGANIZATIONS - Hifffani Chika Aulia; Lira Lestari; Ketleen Metha Setiawan; Dian Prihadini Wibawa (Universitas KH. Abdul Chalim Mojokerto, 2026)
The increasingly diverse global work environment demands that organizations effectively manage diversity to retain qualified employees. One approach is to implement inclusive leadership, which creates a work environment that values ​​diversity and encourages employee engagement. This study aims to examine the role of inclusive leadership in creating a sense of belonging and its implications for employee retention in global organizations. This study uses a literature review method by reviewing various relevant literature sources, such as scientific journal articles and books related to inclusive leadership, diversity, sense of belonging, and employee retention. The results of the study indicate that inclusive leadership plays a crucial role in creating an open work environment that values ​​diversity and provides equal opportunities for all employees. An inclusive work environment can foster a strong sense of belonging in employees, thereby increasing work engagement, organizational commitment, and employee loyalty. Therefore, implementing inclusive leadership is an important strategy for improving employee retention in global organizations.